Southern Escambia County, Florida's Urban Forests - Francisco Escobedo; Sebastian Varela; Christina Staudhammer; Benjamin Thompson (EDIS)
FOR231, a 12-page illustrated fact sheet by Francisco Escobedo, Sebastian Varela, Christina Staudhammer, and Benjamin Thompson, reports on analysis of tree data using USDA Forest Service's Urban Forest Effects (UFORE) model, to help urban foresters, residents, and planners assess several aspects of their urban forests and compare southern Escambia County’s urban forest with forests in other cities in the state of Florida. Includes references. Published by the UF School of Forest Resources and Conservation, December 2009.